Minimal Change Disease as a Secondary and Reversible Event of a Renal Transplant Case with Systemic Lupus Erythematosus - Elena Gkrouzman; Kyriakos A. Kirou; Surya V. Seshan; James M. Chevalier (Case Reports in Nephrology)
Secondary causes of minimal change disease (MCD) account for a minority of cases compared to its primary or idiopathic form and provide ground for consideration of common mechanisms of pathogenesis. In this paper we report a case of a 27-year-old Latina woman, a renal transplant recipient with systemic lupus erythematosus (SLE), who developed nephrotic range proteinuria 6 months after transplantation. The patient had recurrent acute renal failure and multiple biopsies were consistent with MCD. However, she lacked any other features of the typical nephrotic syndrome. An angiogram revealed a right external iliac vein stenosis in the region of renal vein anastomosis, which when restored resulted in normalization of creatinine and relief from proteinuria. We report a rare case of MCD developing secondary to iliac vein stenosis in a renal transplant recipient with SLE. Additionally we suggest that, in the event of biopsy-proven MCD presenting as an atypical nephrotic syndrome, alternative or secondary, potentially reversible, causes should be considered and explored.